Sustainable Urban Green Management Systems: Battery Powered Machines and Equipment - Antonio, P. D.; Scalcione, V. N.; Antonio, C. D. (International Journal For Research In Agricultural And Food Science, 2020)
In the last decades a particular sensitivity has developed towards the issues of urban green management and the use of efficient, safe and sustainable use equipment. The present research was aimed at evaluating the performance and technical reliability of battery-powered machines and equipment. We have experimented with machines such as hedge trimmer, lawn mower, chainsaw and brushcutters, ranges created for gardening. The tests conducted in urban gardens of the city of Matera have highlighted efficient technologies and excellent handling, aspects that contribute to guaranteeing high quality and safety standards. In particular, the possibility of using a single rechargeable lithium-ion battery, has been shown to produce levels of noise and less vibration compared to the levels generated by equipment driven by internal combustion engines, with operating costs and lower maintenance and environmental sustainability ensured.